Meta-Analysis of Contextual Teaching and Learning's (CTL) Effect on Elementary School Students' Critical Thinking Skills - Femmy Nurzulianti Z; Setiawan Edi Wibowo; Vitry Rayani Bethesda Saragih (Universitas Pendidikan Ganesha, 2024)
The Contextual Teaching and Learning approach has been the subject of numerous studies in the past five years that aim especially to improve pupils' critical thinking skills. The purpose of this study is to ascertain how the Contextual Teaching and Learning approach affects a variety of skills, particularly critical thinking. To foster critical thinking in students, teachers need to choose the right teaching method. CTL is a learning process designed to help students understand the meaning of academic material through everyday experiences. The descriptive survey method is used in this study. Data gathering begins in 2019 and ends in 2024. Publish or Perish software is used to extract data from the Scopus database and search engine scholar. There were 200 articles in the whole population, and 16 articles made up the sample that satisfied the requirements. The study's findings include an average effect size of 2.25 for the Contextual Teaching and Learning model, which is categorized as high, and an effect size of 1.34 for the Contextual Teaching and Learning method, which is also classified as high. On the other hand, and the Contextual Teaching and Learning strategy for enhancing critical thinking abilities received a score of 2.09. The information demonstrates that, particularly in elementary schools, the Contextual Teaching and Learning strategy helps enhance students' critical thinking skills.